DIPG-08. ELECTRONIC SEQUENCING PROVIDES OPTIMIZED QUANTIFICATION OF SERIAL, MULTI-GENE MOLECULAR RESPONSE IN THE CSF OF CHILDREN WITH HIGH-GRADE GLIOMA. (4th December 2020) - Bruzek, Amy; Muruganand, Ashwath; Ravi, Karthik; Wadden, Jack; Babila, Clarissa; Tunkle, Leo; Wierzbicki, Kyle; Stallard, Stefanie; Cantor, Evan; Qin, Tingting; Wolfe, Ian; Mody, Rajen; et al.
Abstract: BACKGROUND: For pediatric high-grade glioma (pHGG), non-invasive methods for diagnosis and surveillance are needed. Tumors release DNA (tDNA) into cerebrospinal fluid (CSF), allowing for detection of tumor-associated mutations by CSF sampling. We hypothesized that direct, electronic analysis of tDNA with a novel, hand-held platform (Oxford Nanopore MinION) could quantify patient-specific CSF tDNA variant allele fraction (VAF) with improved speed and limit of detection compared to established methods. METHODS: We integrated required multi-timepoint (0, 2, and 6 months) correlate lumbar punctures (LP) in two ongoing pHGG clinical trials. Using Nanopore technology, we performed amplicon-based PCR on CSF tDNA for recurrent mutations from patient samples (n=19) and normal controls. VAF were determined via MinKNOW, Guppy, MiniMap2, and Integrated Genome Browser. RESULTS: Nanopore CSF tDNA demonstrated improved sensitivity (91%) when compare to NGS sequencing (50%). Nanopore analysis of serially diluted CSF sample demonstrated significantly lower limit of detection (attomolar) than typical NGS sample requirement (nanomolar). H3K27M mutation was reliably detected with 1, 000x depth sequencing, which was achieved in less than 15 minutes of sequencing after amplification. Multiplexed Nanopore analysis of H3F3A and HIST1H3B was employed when H3 status was unknown. Serial CSF tDNA analysis confirmed multi-gene ( H3F3A K27M, PIK3CA, and TP53 ) molecular remission in a 17-year-old with thalamic diffuse midline glioma that correlated with sustained clinical response to ONC201 (14 months and ongoing). CONCLUSIONS: Use of a hand-held, electronic DNA analysis platform allows quantification of multi-gene molecular response with improved speed and limit of detection in the CSF of children with high-grade glioma.